Jus post bellum : mapping the normative foundations - Stahn, Carsten, 1971-; Easterday, Jennifer S.; Iverson, Jens (Oxford : Oxford University Press, 2014)
The successful transition from armed conflict to peace is one of the greatest challenges of contemporary warfare. The laws and principles governing transitions from conflict to peace (jus post bellum) have only recently gained attention in legal scholarship. This book explores the different legal meanings and components of the concept, including its implications in contemporary politics and practice.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 14, 2014).
Keywords: War (International law); Postwar reconstruction -- Law and legislation; Peace-building -- Law and legislation; Politics and Government; International law